An investigation on factors preventing girl-child from further education in rural areas in Federal Capital Territory Abuja - Ogunode Niyi Jacob; Ahaotu Godwin Ndubuisi (Journal of Science and Education (JSE), 2021)
This paper investigates the factors preventing girl-child from further education in rural areas of Federal Capital Territory, Abuja, Nigeria. The study adopted a descriptive survey research design.  The targeted population was all public primary school teachers in rural areas across the six area councils of Abuja Federal Capital Territory. The sample of the study consisted of 300 primary school teachers in thirty public primary schools. The study used simple random sampling, proportionate stratified random sampling, and purposive sampling techniques.  Through a simple random sampling method, 300 teachers were selected from 30 public primary schools across the six area councils of FCT.  The instrument used for data collection was a 15 item structured questionnaire tagged “An Investigation on the Factors Preventing Girl-Child from Further Education Questionnaire” (AIGCPPEEQ). The questionnaire used a 4-point Likert method of strongly agree, agree, disagree, and strongly disagree.  A re-test method with an interval of two weeks was followed to test the reliability of the instrument. The scores obtained were correlated using Pearson’s Product Moment co-efficient. An acceptable coefficient of r=0.86 was obtained, thereby indicating that the instrument was adequate for the study. Additionally, a Cronbach alpha value of r=0.88 was recorded for the instrument indicating its acceptable internal consistency. The data were analyzed using mean and standard deviation for the research questions. The mean cut-off point was 2.5. All items with mean of 2.50 were regarded as agreement and accepted while those less than 2.50 were regarded as disagreement and were accordingly rejected. It concludes that economic, culture, early marriage, religion, distance, inadequate infrastructural facilities, insecurity, poor implementation of Girl-Child right bill, poor funding of Girl Child education and corruption are the factors preventing Girl-child from further education in rural areas in Federal Capital Territory, Abuja, Nigeria.